Національна культурна специфіка фразеологічних компонентів мовної картини світу англійців - Крочук, Юлія Валеріївна; Krochuk, Yu. V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті запропоновано огляд теоретичних положень, присвячених антропоцентричному підходу до вивчення фразеологічного компонента мовної системи; зроблено спробу аналізу фразеологічного корпусу англійської мови на виявлення у ньому національно-маркованих компонентів мовної картини світу британців; встановлено та окреслено провідні ціннісні орієнтири британців у межах концептуального поля PROSPERITY та зібрано фразеологічні одиниці, що їх засвідчують. The article summarizes the review of theoretical statements about the anthropocentric approach to studying language phenomena in general and phraseology in particular. This helped to clear up the fact that language phenomena should be viewed through the prism of the influence made on the language system by national customs, traditions, rituals, beliefs, general culture and national mentality. Thanks to it the author could also investigate the particularities of phraseology’s anthropocentric nature, its ability to embrace different fragments of the language map of the world and fix in its semantics a durable process of national development. The articles shows an attempt to analyze the English phraseological corpus and makes possible to get a notion of the British language picture of the world and reveal its nationally marked components. The author underlines that values take an important place in the British conceptual map of the world. The conducted investigation of the factual material helps to shape the leading British values within the boundaries of the conceptual field PROSPERITY; its key components are presented be the notions ‘money’ and ‘wealth’. The analysis of phraseological units proves the fact that careful behaviour with money, desire to make a fortune and become prosperous – are the principles of life of the British people which are reflected in their traits of character, social and moral norms. And this fact exemplifies national and cultural peculiarities of these values.
National and cultural peculiarities of the English language map of the world
Keywords: фразеологічні одиниці; phraseological units; антропоцентричний підхід; anthropocentric approach; система цінностей; system of values